Influence of biologically active raw materials on rheological properties of flour confectionery products - Chernenkova, Alfiya; Leonova, Svetlana; Chernykh, Valery; Chernenkov, Evgeniy (Acta Biologica Szegediensis, 2020)
New achievements in science, food technologies and medicine call for sounder, scientifically proven nutrition. Food must be functional being aimed at preventing numerous diseases, improving performance capacity and health. Cereals, in particular bakery and confectionery, have the highest potential to be modified to get functional properties. Currently the assortment of this daily food has been actively enlarged. Therefore, the purpose of this work is to improve the production technology of the national flour confectionery "Chak-chak" using biologically active raw materials of the Republic of Bashkortostan. As the result of the conducted studies the ratio of the main ingredients and biologically active raw materials (bee pollen, honey and oat talkan) in flour confectionery as well as production parameters are improved. Therefore, the developed product (chak-chak with bee products and oat talkan), having no analogues, can find its place among other flour confectionery goods.